Alcohol use: prevalence and associated factors in a sample of Tunisian students - R. Ben Soussia; N. Faouel; W. Bouali; E. Gharbi; M. Ben Fredj; L. Zarrouk (European Psychiatry, 2023)
Introduction The use of alcohol, in particular its harmful use and alcohol dependence, represent a public health problem of interest to all age groups. Indeed, alcohol is responsible for a heavy burden of disease and a considerable socio-economic burden. Objectives To determine the prevalence of alcohol use and the main factors associated with it in a sample of Tunisian students. Methods This is an analytical cross-sectional study carried out during the 2020/2021 academic year with a sample of Tunisian students. We used an anonymous self-administered questionnaire distributed online via social networks. Our questionnaire included a section focusing on socio-demographic characteristics and the AUDIT test (Alcohol Use Disorders Identification Test) to detect alcohol addiction. Results Our study enrolled 772 students .The average age of the study population was 23.29 ±3.25.Two hundred ninety-nine students (38.7%) consumed alcohol. The mean age at first use was 18.44 (3.09). Fifty-two alcohol users (17.4%) presented a risk of alcohol dependence. The first consumption contexts were mostly “between friends” (57.4%) and “party time “(23.5%).The main effects sought were the effect of disinhibition (64.5%) and social integration (41.1%) were predominant responses. The determining factors of alcohol consumption were age (p<10-3), male gender (p<10-3), and the presence of grade repetition (p<10-3), wealthy socioeconomic level (p<10-3), and participation in community life (p<10-3). Conclusions Alcohol use and especially alcohol dependence may have harmful effects on student’s life. It is relevant to screen this addiction to better its prevention. Disclosure of Interest None Declared